A simple tele-robotic lunar excavator - Rhaman, Md. Khalilur; Hasan, Shiblee Imtiaz; Hossain, Md. Jonayet; Anik, Kazi Mohammad Razin; Oyon, Mahmudul Hasan; Bhuian, Belal Hossain; Rahman, Md. Mosaddequr (© 2012 IEEE, 2016)
This conference paper was presented in the International Conference on Advanced Computer Science Applications and Technologies, ACSAT 2012; Kuala Lumpur; Malaysia; 26 November 2012 through 28 November 2012 [ © 2012 IEEE] The conference paper's definite version is available at: http://dx.doi.org/10.1109/ACSAT.2012.99